Effect of co-administered inducer or inhibitor on omeprazole pharmacokinetics based on CYP2C19 genotype - Chiaki Kamiya; Naoki Inui; Akio Hakamata; Sachiko Miyakawa; Shimako Tanaka; Shinya Uchida; Noriyuki Namiki; Keiichi Odagiri; Hiroshi Watanabe (Elsevier, 2019)
Polymorphisms of cytochrome P450 (CYP) enzymes can affect enzymatic activity, drug metabolism and drug interactions. Although the potential for drug interactions is especially important when co-administering drugs with strong inductive or inhibitory potential towards drug-metabolizing enzymes, the relationship between CYP genotypes and the extent of the inductive or inhibitory effects remain poorly understood. We investigated the effects of rifampicin (inductive) and fluvoxamine (inhibitory) on metabolism of omeprazole and CYP2C19 enzymatic activity in 19 healthy Japanese subjects. Pharmacokinetic analyses of the CYP2C19 probe drug, omeprazole, were performed before and after rifampicin or fluvoxamine administration. The allele frequencies of the CYP2C19*1, CYP2C19*2 and CYP2C19*3 genotypes were 65.8%, 26.3% and 7.9%, respectively. Subjects with the CYP2C19*1 allele displayed higher levels of omeprazole metabolism than those without the CYP2C19*1 allele. Rifampicin increased omeprazole metabolism in all subjects irrespective of genotype, which suggested that CYP2C19 enzymatic activity was induced by rifampicin administration for all genotypes. Conversely, while fluvoxamine reduced omeprazole metabolism in subjects carrying the CYP2C19*1 allele, it had no impact on omeprazole pharmacokinetics in subjects without this allele. The genotyping of CYP2C19 may be useful for predicting drug interactions with metabolic inhibitors. Keywords: Cytochrome P450 2C19, Drug interaction, Fluvoxamine, Omeprazole, Rifampicin